1989
DOI: 10.1128/jb.171.3.1372-1378.1989
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, purification, and properties of Candida albicans thymidylate synthase

Abstract: The thymidylate synthase (TS) gene was isolated from a genomic Candida albicans library by functional complementation of a Saccharomyces cerevisiae strain deficient in TS. The gene was localized on a 4-kilobase HindIll DNA fragment and was shown to be expressed in a Thy-strain of Escherichia coi. The Thymidylate synthase (TS) has been characterized from a wide variety of organisms and is a proven target in cancer chemotherapy (25). TS should be a good chemotherapeutic target in Candida albicans, a common fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The amino acid sequence shows both of the invariant eukaryote-specific insertions; a 12-amino acid loop at position 90 (between a-D and E helices) and the 8-amino acid loop after residue 157 (between a-G and H helices) of the L. casei TS. The single-amino acid insertion after residue 34 has thus far been observed only in the other fungal TSs characterized (serine in P. carinii, proline in S. cerevisiae and Candida albicans) (15,34). This insertion is found in the first 3-strand of TS, which forms an important interface for subunit contact.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The amino acid sequence shows both of the invariant eukaryote-specific insertions; a 12-amino acid loop at position 90 (between a-D and E helices) and the 8-amino acid loop after residue 157 (between a-G and H helices) of the L. casei TS. The single-amino acid insertion after residue 34 has thus far been observed only in the other fungal TSs characterized (serine in P. carinii, proline in S. cerevisiae and Candida albicans) (15,34). This insertion is found in the first 3-strand of TS, which forms an important interface for subunit contact.…”
mentioning
confidence: 99%
“…Translation of the open reading frame yields a polypeptide of 297 amino acids with a molecular weight of 34,269. The deduced amino acid sequence shows conservation of all the amino acid residues that are invariant in known TSs.…”
mentioning
confidence: 99%
“…The earliest molecular biological studies in C. albicans suggested that Candida genes were likely to resemble genes in Saccharomyces cerevisiae, since most C. albicans genes were cloned via the complementation of S. cerevisiae mutations [3,14,32,33,34,62,69]. Many C. albicans genes will express directly in Escherichia coli [14,23,34] and more recently the suspected similarity between C. albicans and S. cerevisiae genes has been confirmed by DNA sequence analysis.…”
Section: Gene Structurementioning
confidence: 96%
“…The C. albicans thymidylate synthase gene was cloned by its ability to complement a tmp 1 mutation in S. cerevisiae [69]. The gene encodes a protein of 315 amino acids which, when expressed in E. coli, was enzymatically indistinguishable from the enzyme purified from C. albicans.…”
Section: Thymidylate Synthasementioning
confidence: 99%
See 1 more Smart Citation